Violence, living standards, and inequality in modern times - Rutar, Tibor (Retrospektive, 2025)
This paper examines the recent debates surrounding the “New Optimists,” who argue that the last few centuries have witnessed unprecedented human progress, particularly in terms of rising living standards. Their critics, by contrast, emphasize the persistence of violence and the continued presence of high inequality in modern societies. Using long-run cross-national data on war deaths, homicide, income, and inequality, the paper finds that violence remains low and relatively contained, real after--tax incomes for the world’s bottom half have more than doubled, and inequality has stabilized or declined since around 2005. Statistical analyses further show that improvements in property rights, the rule of law, and free trade consistently precede sustained increases in GDP per capita. Progress is neither teleological nor inevitable, but it is measurable, broadly ongoing, and closely tied to open economic and political institutions.
Keywords: inequality; living standards; napredek; nasilje; neenakost; New Optimists; novi optimisti; Pinker, Steven; progress; violence; življenski standard